Manual for Ensuring Privacy, Confidentiality, and Secure Data Storage - Czechowski, Konrad; Sylvestre, John (Université d'Ottawa | University of Ottawa, 2018)
This document outlines the Centre for Research on Educational and Community Services’ (CRECS) recommended procedures for collecting, safeguarding, and working with confidential data. As a research centre located at the University of Ottawa, CRECS must hold itself to the highest standards for protection of personal information and confidential information. CRECS researchers, students and postdoctoral fellows regularly have access to confidential information such as personally-identifiable information, health information, and other kinds of non-public information. As a research centre, it is essential that CRECS be able to assure both its institutional partners and research participants of the safety and confidentiality of the data they provide. The smallest lapse in vigilance may have consequences for the participants, CRECS, the University of Ottawa, or our community and institutional partners. It is the responsibility of everyone at CRECS to treat data security as a vital part of their work. This manual begins with a rationale for maintaining privacy, confidentiality, and data security. Then, there is a brief description of how information for this manual was collected. Next, a review of applicable provincial and federal privacy legislation as well as professional codes of conduct is presented. Based on this review, a list of recommendations regarding privacy, confidentiality, and data security are provided.
Keywords: cybersecurity; data protection